2021
DOI: 10.21926/rpm.2103033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recycled Rubber Particles on the Deicing Salt-Scaling Durability of Concrete

Abstract: The present study investigated the effect of reused rubber particles (RRP) on the deicer salt durability of ordinary concrete. Four mixtures were designed, a control concrete (CC) and three other rubber concretes obtained by partial substitution of natural dune sand aggregate with reused rubber particles with 0%, 3%, 6%, and 9% w/w. All studied concretes were subjected to the combined effect of freeze/thaw (56 and 120) cycles with the deicer salt solution of 3% NaCl. The results indicated that RRP improved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This research revealed that RATW reduced the mechanical performance of composites incorporating rubber aggregate compared to reference concrete [14,15,16]. Other studies indicated that RATW improved the rubber-cement composite behavior, such as: water absorption by capillarity, thermal conductivity, strain capacity, ductility 2 compared to control mix [17,18,9]. Recent research revealed that RATW increasing air content into fresh rubber mixes [19,23].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This research revealed that RATW reduced the mechanical performance of composites incorporating rubber aggregate compared to reference concrete [14,15,16]. Other studies indicated that RATW improved the rubber-cement composite behavior, such as: water absorption by capillarity, thermal conductivity, strain capacity, ductility 2 compared to control mix [17,18,9]. Recent research revealed that RATW increasing air content into fresh rubber mixes [19,23].…”
Section: Introductionmentioning
confidence: 87%
“…However, we noticed that the test conditions of these studies (the maximum freezing temperature, number of cycle) were insufficient to assess the freeze-thaw resistance of rubber composite. Concerning the deicing salt attack, recent study conducted by Guelmine and Hadjab [18] reported that RATW highly increased the deicing salt-scaling resistance of rubber concrete compared to control.…”
Section: Introductionmentioning
confidence: 99%
“…This waste pollutes the natural sources of air, groundwater, and soil, because it contains polluted and toxic elements such as heavy metals [1][2][3]. Reliable environmental references recommended reusing them with building materials as a concrete aggregate [2][3][4][5]. However, many studies have shown that the inclusion of rubber particles with concrete composite produced a high reduction in their mechanical performance [6,7].…”
Section: Introductionmentioning
confidence: 99%